2018
DOI: 10.1016/j.jmbbm.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Over length quantification of the multiaxial mechanical properties of the ascending, descending and abdominal aorta using Digital Image Correlation

Abstract: In this paper, we hypothesize that the biaxial mechanical properties of the aorta may be dependent on arterial location. To demonstrate any possible position-related difference, our study analyzed and compared the biaxial mechanical properties of the ascending thoracic aorta, descending thoracic aorta and infrarenal abdominal aorta stemming from the same porcine subjects, and reported values of constitutive parameters for well-known strain energy functions, showing how these mechanical properties are affected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 61 publications
(101 reference statements)
2
10
0
Order By: Relevance
“…The range of maximum principal stress σ * at a physiological in vivo pressure of 150 mmHg was between 0.12 and 0.25 MPa and that of maximum principal strain E * ranged between 0.12 and 0.95, highlighting a marked local heterogeneity of the mechanical properties. Previous studies already underlined this point with similar experiments on ATAAs (Romo et al, 2014; Davis et al, 2015, 2016; Trabelsi et al, 2015; Duprey et al, 2016) or other biaxial tests on aortic tissue (Bersi et al, 2016; Peña et al, 2018). However, the major limitation of the aforementioned studies was to assume a homogeneous wall thickness, which could alter the calculation of stresses as clearly emphasized from Figure 7.…”
Section: Discussionmentioning
confidence: 75%
“…The range of maximum principal stress σ * at a physiological in vivo pressure of 150 mmHg was between 0.12 and 0.25 MPa and that of maximum principal strain E * ranged between 0.12 and 0.95, highlighting a marked local heterogeneity of the mechanical properties. Previous studies already underlined this point with similar experiments on ATAAs (Romo et al, 2014; Davis et al, 2015, 2016; Trabelsi et al, 2015; Duprey et al, 2016) or other biaxial tests on aortic tissue (Bersi et al, 2016; Peña et al, 2018). However, the major limitation of the aforementioned studies was to assume a homogeneous wall thickness, which could alter the calculation of stresses as clearly emphasized from Figure 7.…”
Section: Discussionmentioning
confidence: 75%
“…In that work, Peña et al [5], found that the aorta was stiffer in the ascending region than the distal region. In the murine aorta, the longitudinal stretch ratio, which is a parameter that describes the ratio of the aorta length during loading and zero-stress, has been found to increase linearly from the ascending aorta to the distal abdominal aorta [11].…”
Section: Introductionmentioning
confidence: 91%
“…Rupture abdominal aortic aneurysm is a leading cause of death in men over 65 years old [2], a problem exacerbated with the ageing population. It is for this reason that there is substantial interest in the biomechanical behaviour of the aorta [3][4][5]. Biomechanical studies can aid risk evaluation of aortic pathologies and ultimately aid surgical planning and clinical care [4,6].…”
Section: Introductionmentioning
confidence: 99%
“…These tissues were not randomly chosen. It is well known that the behaviour of the ascending aorta could be considered quasi-isotropic from the point of view of biaxial tests (similar response for circumferential and longitudinal directions) [38]. However, the pulmonary artery has a strongly anisotropic behaviour.…”
Section: Biaxial Experimentsmentioning
confidence: 99%